2008
DOI: 10.1111/j.1600-0501.2008.01620.x
|View full text |Cite
|
Sign up to set email alerts
|

Implants in fresh extraction sockets: a prospective 5‐year follow‐up clinical study

Abstract: It was demonstrated that 'immediate implants' that were loaded after 5-7 months had a high success rate. During the 5-year interval, no implant was lost, and the mean Rx bone level at the implants was maintained or even improved. The plaque and mucositis scores were low (<20%) at baseline and at all re-examinations. Implant sites located adjacent to the teeth showed bone gain during the initial period while sites that were facing edentulous zones lost some bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
132
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(164 citation statements)
references
References 27 publications
26
132
0
6
Order By: Relevance
“…Berglundh et al (2005) analyzed marginal bone alterations following implant placement, abutment connection, and functional loading; they reported that the largest amount of bone loss occurred following implant placement and abutment connection and that almost no bone level alterations occurred after. These findings are in accordance with our results and other clinical reports (Botticelli et al, 2008;Nisapakultorn et al, 2010;Valentini et al, 2010). The results of the present study indicate that insertion of immediately loaded implants in fresh extraction sockets (group II) result in significant reduction of resorption of marginal ridge.…”
Section: Discussionsupporting
confidence: 95%
“…Berglundh et al (2005) analyzed marginal bone alterations following implant placement, abutment connection, and functional loading; they reported that the largest amount of bone loss occurred following implant placement and abutment connection and that almost no bone level alterations occurred after. These findings are in accordance with our results and other clinical reports (Botticelli et al, 2008;Nisapakultorn et al, 2010;Valentini et al, 2010). The results of the present study indicate that insertion of immediately loaded implants in fresh extraction sockets (group II) result in significant reduction of resorption of marginal ridge.…”
Section: Discussionsupporting
confidence: 95%
“…Chen & Buser (2009) also observed a lower frequency of advanced gingival recession in thick biotypes. Boticelli et al (2008) reported slightly greater midfacial recession at implants placed in the mandible (1.2 ± 1.8mm) than at maxillary sites (0.2 ± 1mm).…”
Section: Aesthetic Outcomes In Immediate Implantsmentioning
confidence: 87%
“…When analysing bone dimensional changes three methods have been employed: clinical intrasurgical measurements by means of a re-entry procedure (Gher et al 1994;Boticelli et al 2004Boticelli et al , 2008Chen et al 2007;Ferrus et al 2010) or radiographic measurements on CBCTs (Roe et al 2012;Benic et al 2012;Degidi et al 2012;Assaf et al 2013;Morimoto et al 2015) or periapical radiographs Valentini et al 2010;Cosyn et al 2013;Covani et al 2014). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Botticelli et al 27,28) reported that the bone level was recovered when the alveolar bone defect was equal to or less than 2 mm. No matter how small a defect is, this suggests that space where a blood vessel and a cell can communicate is required.…”
Section: Discussionmentioning
confidence: 99%